Evaluation of the impact of the European Code against Cancer on awareness and attitudes towards cancer prevention at the population and health promoters' levels. (April 2021) - Ritchie, D.; Mallafré-Larrosa, M.; Ferro, G.; Schüz, J.; Espina, C.
Highlights: Awareness of the European Code against Cancer varies significantly by country. Gender did not seem to play a strong role on cancer prevention literacy. The European Code against Cancer is used as a tool for health policy development. A further, systematic evaluation of the European Code against Cancer is required. Abstract: Introduction: The European Code against Cancer (ECAC) informs the public on steps to take to reduce their cancer risk. Despite over three decades of promotion, no systematic evaluation of its impact has yet been carried out. This study aimed to address the gap in knowledge regarding the impact of the ECAC. Methods: An online survey targeting adults in the general population was conducted and analysed by age, gender, and country, both descriptive and mutually adjusted in logistic regression analyses. Additionally, semi-structured interviews with health promotion professionals from not-for-profit organisations in Europe were conducted and a qualitative thematic analysis was carried out for each interview. Results: 8171 people from eight European countries responded to the survey. Although 70 % of respondents were aware of cancer prevention guidance, a low percentage of participants had previously heard about the ECAC (2% in UK to 21 % in Hungary and Poland). Females were more likely to make lifestyle changes to reduce their risk of cancer (odds ratio = 1.17; 95 % confidence interval: 1.05–1.29). Twenty-eight online semi-structured interviews with professionals were conducted covering 25 countries. Regional variation in the methods and target groups of the promotion and dissemination of the ECAC was reported. Conclusion: Whilst familiarity with the ECAC in the general public is low, professionals frequently use it as a basis for informing population-level actions. Future editions should be accompanied by a systematic evaluation of the ECAC investigating the impact upon society.